Beta‐catenin participates in dialysate‐induced peritoneal fibrosis via enhanced peritoneal cell epithelial‐to‐mesenchymal transition. Issue 2 (19th January 2017) - Ji, Shuiyu; Deng, Hao; Jin, Wei; Yan, Pengpeng; Wang, Rending; Pang, Lisha; Zhou, Jingyi; Zhang, Jiaming; Chen, Xiaoying; Zhao, Xiang; Shen, Jia
Abstract : Long‐term exposure to peritoneal dialysate with high glucose (HG) leads to peritoneal fibrosis and thus decreases dialysis efficiency. In this study, we explored the role of β‐catenin in this process. C57BL/6 mice received daily intraperitoneal injection with 10% of the body weight of saline (control), 4.25% glucose peritoneal dialysis fluid (PDF), or PDF combined with 5 mg·kg −1 of the β‐catenin inhibitor ICG‐001 (PDF+ICG) for 30 days. Also, mice peritoneal epithelial cells (mPECs) were cultured in 4.25% glucose (HG) or combined with 10 μm ICG‐001 (HG+ICG) for 48 h. We found greater thickness of the parietal peritoneum in the PDF‐treated mice. Additionally, lower expression of E‐cadherin, higher expression of Vimentin, β‐catenin, and Snail, and activation of β‐catenin was observed in the mice and in HG‐treated mPECs, all of which were reversed by ICG‐001. The changes in E‐cadherin and Vimentin indicated occurrence of the epithelial‐to‐mesenchymal transition (EMT). Thus, β‐catenin signaling participates in the process of HG‐induced peritoneal fibrosis, and the EMT of peritoneal epithelial cells is one of the underlying mechanisms of this pathological change. Abstract : This study explored the role of β‐catenin in the process of peritoneal fibrosis induced by long‐term exposure to peritoneal dialysate with high glucose. We showed a greater thickness of the parietal peritoneum in the mice treated with 4.25% glucose (HG) peritoneal dialysis fluid, as well as biomarkers related to epithelial‐to‐mesenchymal transition, all of which were reversed by β‐catenin inhibitor ICG‐001.